Refugee and Asylum Seeker Trauma Informed Care Training for Oral Healthcare Professionals in NSW, Australia - Siobhan Kelton; Kanchan Marcus; Graeme Liston; Angela Masoe; Woosung Sohn (Frontiers Media S.A., 2022)
People from refugee and asylum seeker (RAS) backgrounds who have re-settled in Australia experience inequitable health outcomes. As a result, people from RAS backgrounds need access to culturally safe and responsive care. To provide this care, oral health professionals must understand how experiences of trauma influence a patient's oral health. The aim of this study was to highlight the lessons learnt from providing trauma informed care (TIC) to oral health professionals in New South Wales (NSW). TIC is a model that emphasises trust, patient safety, choice and empowerment to foster healthcare equity. This study was designed and piloted by the Centre for Oral Health Strategy (COHS), NSW Ministry of Health in partnership with NSW Refugee Health Service, local Multicultural Health Services, and four Local Health Districts (LHDs): Hunter New England, Mid-North Coast, Murrumbidgee and Illawarra Shoalhaven. Pre and post TIC training surveys were distributed to oral health professionals. This captured baseline versus intervention data to understand their knowledge of TIC. Seven training sessions were provided by NSW Refugee Health Service in four LHDs. A total of 152 participants attended a TIC training session, 106 participants completed the pre-survey, and 67 participants completed the post-survey. At baseline, only 50% of staff reported confidence in delivering TIC care to RAS populations. After the intervention, 97% of staff reported feeling extremely, very, or somewhat confident in understanding and delivering TIC. Findings demonstrate that TIC training can support oral health professionals to provide culturally safe and responsive care to people from RAS backgrounds.